Analysis of the Incidence of Acute Respiratory Infections in Children Under Five at Community Health Centres - Irsa Taponi; Arie Wahyudi; Chairil Zaman (Lentera Perawat, 2024)
There are still high cases of ARI in children under five, ARI is one of the 10 most common diseases in the first place in health services at the health centre. This study aims to determine the factors associated with the incidence of ARI in children under five at the Pegayut Health Centre, Ogan Ilir Regency in 2024.  Quantitative analytical survey research design with a cross-sectional approach. The sampling technique used purposive sampling technique, using the slovin formula. The research sample totalled 80 respondents. Inclusion criteria are parents of children under five who visit for treatment at the Puskesmas, while the exclusion criteria are parents of children under five who are not willing to be respondents. This study was conducted on 01-28 February 2024 Data collection techniques by interview using questionnaire r. Bivariate data analysis using chi-Square test and multivariate logistic regression. The results showed that there was a relationship between occupation (p value 0.005), smoking behaviour (p value 0.017), the use of mosquito repellent (p value 0.04), the use of stove cooking utensils (p value 0.005) and the distance between the house and the highway (p value 0.02) to the incidence of ARI in children under five at the Pegayut Health Centre, Ogan Ilir Regency in 2024.  The most dominant factor with the incidence of ARI in children under five at the Pegayut Health Centre, Ogan Ilir Regency in 2024 is smoking behaviour in the house (p value 0.016), (OR 0.140). The conclusion is that there is a relationship between employment, smoking behaviour, the use of mosquito repellents, the use of stove cooking utensils and the distance of the house from the highway to the incidence of ARI in children under five at the Pegayut Health Centre. Suggestions for the Puskesmas provide education related to smoking behaviour in the community, with existing programs and activities at the Puskesmas.